2005
DOI: 10.1111/j.1744-7909.2005.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Radiation Suppresses the Growth and Antioxidant Systems of Two Marine Microalgae,Platymonas subcordiformis(Wille) Hazen andNitzschia closterium(Ehrenb.) W. Sm

Abstract: This study investigated whether increased solar UV-B radiation (280−315 nm) could suppress the growth of marine microalgae through effects on their antioxidant systems. Two marine microalgae species, Platymonas subcordiformis (Wille) Hazen and Nitzschia closterium (Ehrenb.) W. Sm, were exposed to a range of UV-B radiation and both showed reductions in their growth rates, and the chlorophyll a (Chl a) and carotenoid (Car) contents when UV-B radiation dose increased. Superoxide anion radical (O 2 -. ) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…Differences in all growth responses measured during the exposures occurred mainly after long-term exposure to PAR+UV-A+UV-B. Nielsen & Ekelund (1995) and Zhang et al (2005) have reported similar results for some phytoplankton diatoms, but due to differences in the experimental set up, their results are difficult to compare with ours. In plants, UV-B damage has been observed at low radiation doses, causing a general decrease in protein synthesis and mRNA transcripts for proteins involved in chloroplasts and photosynthesis (Strid et al, 1994).…”
Section: Effects On Growth Chl a And Protein Contentmentioning
confidence: 59%
See 1 more Smart Citation
“…Differences in all growth responses measured during the exposures occurred mainly after long-term exposure to PAR+UV-A+UV-B. Nielsen & Ekelund (1995) and Zhang et al (2005) have reported similar results for some phytoplankton diatoms, but due to differences in the experimental set up, their results are difficult to compare with ours. In plants, UV-B damage has been observed at low radiation doses, causing a general decrease in protein synthesis and mRNA transcripts for proteins involved in chloroplasts and photosynthesis (Strid et al, 1994).…”
Section: Effects On Growth Chl a And Protein Contentmentioning
confidence: 59%
“…Data are expressed as mg 100 g Jaleel et al, 2009). One of the important features of antioxidant enzymes is their inducibility under conditions of oxidative stress, and such induction could be an important adaptation to UV-B radiation stress (Rijstenbil, 2002;Zhang et al, 2005). Furthermore, microalgae are damaged when the UV-B dose is relatively high and the production of protective enzymes is reduced, so the antioxidant systems cannot scavenge the excess active oxygen (Rijstenbil, 2002).…”
Section: Activities Of Antioxidant Defence Enzymesmentioning
confidence: 99%
“…The concentration of MDA reflects the extent of lipid peroxidation in the cell membrane under stress conditions (Zhang et al 2005). In the current research, the injury of biological lipids by ROS, as indicated by MDA content, was clearly detected in the submerged and non-submerged plants (Fig.…”
Section: Damage After Subjection To Different Submergencementioning
confidence: 99%
“…It has been shown that the detrimental effects of UV-B radiation on microalgae are always mediated by free radicals which induce oxidative stress (Janknegt et al 2008;Wang et al 2007). Fortunately antioxidant systems in microalgae can scavenge reactive oxygen species (ROS), including the antioxidant molecules such as carotenoids, tocopherols, ascorbate, and reduced glutathione, and antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) (Janknegt et al 2008;Zhang et al 2005). Our previous studies showed that the exposure of Antarctic ice microalgae to UV-B under laboratory conditions, affected their morphology and ultrastructure (Liu et al 2004), main biochemical composition ) and UV-B induced substances (Miao et al 2002).…”
Section: Introductionmentioning
confidence: 99%